Amorphous silicon / microcrystalline silicon laminated solar cell and manufacturing method thereof

The novel amorphous silicon/microcrystalline silicon tandem solar cell structure addresses current matching and degradation issues by optimizing film thicknesses and doping concentrations, achieving high efficiency and stability.

CN111554762BActive Publication Date: 2024-12-20HENAN POLYTECHNIC INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010399817.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-05-05
Publication Date
2024-12-20
Estimated Expiration
2040-05-05

AI Technical Summary

Technical Problem

The performance of amorphous silicon/microcrystalline silicon tandem solar cells is limited by the current matching degree of the top and bottom cells, and the amorphous silicon material's light-induced degradation leads to a decline in photoelectric conversion performance over time.

Method used

A novel solar cell structure with a connecting layer that reduces the reverse barrier effect and optimizes light absorption, featuring specific thicknesses and doping concentrations of silicon films to improve current density matching and stability.

Benefits of technology

The new structure achieves a conversion efficiency of 12.9% with a light-induced degradation rate of 7.5% over 1000 hours, enhancing the stability and efficiency of the tandem solar cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111554762B_ABST
    Figure CN111554762B_ABST
Patent Text Reader

Abstract

The present invention discloses an amorphous silicon / microcrystalline silicon stacked solar cell and a manufacturing method thereof. According to the preparation order, the solar cell structure is composed of a flexible transparent substrate, a front electrode, an amorphous silicon top cell, a connecting layer, a microcrystalline silicon bottom cell, and a back electrode. The present invention uses a connecting layer to connect the top cell and the bottom cell in series, which can optimize the light absorption ratio of the sub-cells and is beneficial for the photogenerated carriers to overcome the reverse potential barrier at the sub-cell interface, thereby achieving matching of the short-circuit current density of the top cell and the bottom cell while reducing the thickness of the amorphous silicon top cell. On the one hand, the overall short-circuit current density of the solar cell is increased, and the photoelectric conversion efficiency of the solar cell is improved. On the other hand, the light-induced degradation effect of the amorphous silicon top cell is weakened, and the stability of the cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaic power generation, and in particular is an amorphous silicon / microcrystalline silicon stacked solar cell and a manufacturing method thereof. Background Art

[0002] Amorphous silicon / microcrystalline silicon (a-Si:H / μc-Si:H) tandem solar cells are composed of an amorphous silicon top cell with an optical band gap of about 1.70eV and a microcrystalline silicon bottom cell with an optical band gap of about 1.10eV connected in series. This tandem structure broadens the spectral response range of the solar cell and improves the utilization rate of sunlight.

[0003] However, the performance of tandem solar cells is not only related to the photoelectric conversion capacity of the top and bottom cells, but also largely limited by the current matching degree of the top and bottom cells. The overall short-circuit current density of the tandem solar cell depends on the short-circuit current density of the smallest sub-cell. In addition, due to the light-induced degradation phenomenon of the amorphous silicon material itself, the overall photoelectric conversion performance of the tandem solar cell will decline with the illumination time.

[0004] Therefore, the main technical problems faced by amorphous silicon / microcrystalline silicon tandem solar cells are, first, to improve the matching degree of short-circuit current density between the top and bottom cells to improve the efficiency of the tandem solar cells; second, to reduce the thickness of the amorphous silicon top cell to improve the stability of the photoelectric conversion performance of the tandem solar cells. Summary of the invention

[0005] In view of the main problems of the above-mentioned tandem solar cells, the present invention proposes a novel amorphous silicon / microcrystalline silicon tandem solar cell structure, which connects the top cell and the bottom cell in series through a connecting layer, reduces the reverse barrier effect at the interface between the top cell and the bottom cell, optimizes the light absorption ratio of the top cell and the bottom cell, thereby reducing the thickness of the top cell, and improving the matching degree of short-circuit current density of the top and bottom cells, to obtain a tandem solar cell with high conversion efficiency and high stability. Most importantly, it obtains the optimal structural parameters of the connecting layer and the optimal thickness of the top and bottom cells.

[0006] In order to achieve the above-mentioned object, the present invention provides an amorphous silicon / microcrystalline silicon stacked solar cell. In accordance with the preparation order, the solar cell is composed of a flexible transparent polyimide substrate, an aluminum-doped ZnO film, a first p-type silicon film, a first intrinsic silicon film, a first n-type silicon film, a second n-type silicon film, a boron-doped ZnO film, a second p-type silicon film, a third p-type silicon film, a second intrinsic silicon film, a third n-type silicon film and a metal Al film.

[0007] The manufacturing method of an amorphous silicon / microcrystalline silicon tandem solar cell described in the present invention comprises the following specific steps:

[0008] (1) Substrate installation and cleaning;

[0009] The flexible transparent polyimide film is cut into a suitable size and tightened on the mold. The mold is placed in a cleaning container and deionized water is added. The container is placed in an ultrasonic cleaner and cleaned twice, each for 15 minutes. After taking it out, the polyimide substrate and the mold are blown dry with a nitrogen gun and placed in an oven for drying.

[0010] (2) preparing the front electrode;

[0011] The mold was loaded into a DC target magnetron sputtering system to complete the preparation of the front electrode aluminum-doped ZnO film.

[0012] (3) preparing a first p-type silicon thin film;

[0013] The mold is loaded onto the support of the loading chamber of the plasma chemical vapor deposition system, and after the vacuum degree reaches the standard, it is transferred to the p-type amorphous silicon material deposition chamber to complete the preparation of the first p-type silicon film of the top battery.

[0014] (4) preparing a first intrinsic silicon thin film;

[0015] The residual gas is extracted with a vacuum pump, and after the vacuum degree reaches the standard, it is transferred to the intrinsic amorphous silicon material deposition chamber to complete the preparation of the first intrinsic silicon film of the top battery.

[0016] (5) preparing a first n-type silicon thin film;

[0017] The residual gas is extracted with a vacuum pump, and after the vacuum degree reaches the standard, it is transferred into the n-type amorphous silicon material deposition chamber to complete the preparation of the first n-type silicon film of the top battery.

[0018] (6) preparing a second n-type silicon thin film;

[0019] The residual gas is extracted by a vacuum pump, and after the vacuum degree reaches the standard, it is transferred into the n-type microcrystalline silicon material deposition chamber to complete the preparation of the second n-type silicon film of the connecting layer.

[0020] (7) Preparation of boron-doped ZnO thin films;

[0021] The mold is taken out from the loading chamber of the plasma chemical vapor deposition system and placed in the metal organic chemical vapor deposition system to complete the preparation of the boron-doped ZnO film of the connecting layer.

[0022] (8) preparing a second p-type silicon thin film;

[0023] The mold is taken out from the metal organic chemical vapor deposition system, loaded onto the support of the plasma chemical vapor deposition system loading chamber, and transferred to the p-type microcrystalline silicon material deposition chamber after the vacuum degree reaches the standard to complete the preparation of the second p-type silicon film of the connecting layer.

[0024] (9) preparing a third p-type silicon thin film;

[0025] The concentration of reactants is adjusted to continuously deposit and the preparation of the third p-type silicon film of the bottom cell is completed.

[0026] (10) preparing a second intrinsic silicon thin film;

[0027] The residual gas is extracted with a vacuum pump, and after the vacuum degree reaches the standard, it is transferred to the intrinsic microcrystalline silicon material deposition chamber to complete the preparation of the second intrinsic silicon film of the bottom battery.

[0028] (11) preparing a third n-type silicon thin film;

[0029] The residual gas is extracted with a vacuum pump, and after the vacuum degree reaches the standard, it is transferred to the n-type amorphous silicon material deposition chamber to complete the preparation of the third n-type silicon film of the bottom battery.

[0030] (12) Preparation of metal Al thin film;

[0031] The mold is taken out from the loading chamber of the plasma chemical vapor deposition system and placed in the metal thermal evaporation system to complete the preparation of the back electrode metal Al film.

[0032] Wherein, the thickness of the first n-type silicon film is 4 nm;

[0033] The second n-type silicon film is an n-type hydrogenated microcrystalline silicon film with a thickness of 22 nm and a doping concentration of 5.7×10 18 cm -3 ;

[0034] The thickness of the boron-doped ZnO film is 40 nm, and the doping concentration is 5.8×10 19 cm -3 ;

[0035] The thickness of the second p-type silicon film is 19 nm, and the doping concentration is 1.0×10 19 cm -3 ;

[0036] The thickness of the third p-type silicon film is 3 nm;

[0037] The effective area of ​​the solar cell is 2.6 cm 2 , the top cell thickness is 275nm and the bottom cell thickness is 2680nm.

[0038] The present invention adopts a novel amorphous silicon / microcrystalline silicon stacked solar cell structure, improves the short-circuit current density mismatch problem between the top and bottom cells, improves the photoelectric conversion performance of the stacked solar cell, and achieves a conversion efficiency of 12.9%; reduces the thickness of the amorphous silicon top cell to 275nm, improves the light stability of the stacked solar cell, and the light-induced degradation rate is within 7.5% for 1000h. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram of the amorphous silicon / microcrystalline silicon stacked solar cell structure proposed by the present invention. DETAILED DESCRIPTION

[0040] In order to more clearly explain the technical problems, technical solutions and beneficial effects solved by the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0041] Example S1

[0042] like Figure 1 An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0043] In the stacked solar cell S1, the thickness of the first n-type silicon film is 4 nm, the thickness of the second n-type silicon film is 22 nm, the thickness of the second p-type silicon film is 19 nm, and the thickness of the third p-type silicon film is 3 nm.

[0044] Comparative Examples T1-1 to T1-8

[0045] The preparation of the stacked solar cells T1-1 to T1-8 is changed to the structure described in the following Table 1. Compared with the stacked solar cell S1, only the thickness of the first n-type silicon film, the second n-type silicon film, the second p-type silicon film and the third p-type silicon film are adjusted. Otherwise, the stacked solar cells T1-1 to T1-8 are prepared by the same method as the stacked solar cell S1.

[0046] Table 1 Structure and performance test results of tandem solar cells S1 and T1-1~T1-8

[0047]

[0048] Notes to Table 1: A film with a thickness of “0” means that the layer is not included in the structure of the tandem solar cell.

[0049] It can be seen from Table 1 that the stacked solar cell structure including the first n-type silicon film, the second n-type silicon film, the second p-type silicon film and the third p-type silicon film has higher performance, and the optimal thicknesses of the first n-type silicon film and the third p-type silicon film in the stacked solar cell structure are 4nm and 3nm, respectively.

[0050] Example S2

[0051] like Figure 1 An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0052] In the stacked solar cell S2, the second n-type silicon thin film is an n-type hydrogenated microcrystalline silicon thin film.

[0053] Comparative Examples T2-1 to T2-4

[0054] The preparation of the stacked solar cells T2-1 to T2-4 is changed to the structure described in the following Table 2. Compared with the stacked solar cell S2, the material type of the second n-type silicon film is adjusted to an n-type hydrogenated amorphous silicon film, and the thickness of the n-type hydrogenated amorphous silicon film is adjusted. Other than this, the stacked solar cells T2-1 to T2-4 are prepared by the same method as the stacked solar cell S2.

[0055] Table 2 Structure and performance test results of tandem solar cells S2 and T2-1~T2-4

[0056]

[0057] It can be seen from Table 2 that in the stacked solar cell structure, a higher conversion efficiency can be obtained by using an n-type hydrogenated microcrystalline silicon film as the second n-type silicon film than an n-type hydrogenated amorphous silicon film.

[0058] Example S3

[0059] like Figure 1An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0060] In the stacked solar cell S3, the thickness of the second n-type silicon thin film is 22 nm.

[0061] Comparative Examples T3-1 to T3-3

[0062] The preparation of the stacked solar cells T3-1 to T3-3 was changed to the structure described in the following Table 3. Compared with the stacked solar cell S3, only the thickness of the second n-type silicon film was adjusted. Other than that, the stacked solar cells T3-1 to T3-3 were prepared by the same method as the stacked solar cell S3.

[0063] Table 3 Structure and performance test results of tandem solar cells S3 and T3-1~T3-3

[0064]

[0065] It can be seen from Table 3 that in the stacked solar cell structure, the optimal thickness of the second n-type silicon film is 22 nm.

[0066] Example S4

[0067] like Figure 1An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0068] In the tandem solar cell S4, the doping concentration of the second n-type silicon film is 5.7×10 18 cm -3 .

[0069] Comparative Examples T4-1 to T4-3

[0070] The preparation of the stacked solar cells T4-1 to T4-3 was changed to the structure described in the following Table 4. Compared with the stacked solar cell S4, only the doping concentration of the second n-type silicon film was adjusted. Other than that, the stacked solar cells T4-1 to T4-3 were prepared using the same method as the stacked solar cell S4.

[0071] Table 4 Structure and performance test results of tandem solar cells S4 and T4-1~T4-3

[0072]

[0073] It can be seen from Table 4 that the optimal doping concentration of the second n-type silicon film in the tandem solar cell structure is 5.7×10 18 cm -3 .

[0074] Example S5

[0075] like Figure 1An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0076] In the stacked solar cell S5, the thickness of the second p-type silicon thin film is 19 nm.

[0077] Comparative Examples T5-1 to T5-3

[0078] The preparation of the stacked solar cells T5-1 to T5-3 is changed to the structure described in the following Table 5. Compared with the stacked solar cell S5, only the thickness of the second p-type silicon film is adjusted. Other than this, the stacked solar cells T5-1 to T5-3 are prepared by the same method as the stacked solar cell S5.

[0079] Table 5 Structure and performance test results of tandem solar cells S5 and T5-1~T5-3

[0080]

[0081] It can be seen from Table 5 that in the stacked solar cell structure, the optimal thickness of the second p-type silicon film is 19 nm.

[0082] Example S6

[0083] like Figure 1An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0084] In the tandem solar cell S6, the doping concentration of the second p-type silicon film is 1.0×10 19 cm -3 .

[0085] Comparative Examples T6-1 to T6-3

[0086] The preparation of the stacked solar cells T6-1 to T6-3 was changed to the structure described in the following Table 6. Compared with the stacked solar cell S6, only the doping concentration of the second n-type silicon film was adjusted. Other than that, the stacked solar cells T6-1 to T6-3 were prepared using the same method as the stacked solar cell S6.

[0087] Table 6 Structure and performance test results of tandem solar cells S6 and T6-1~T6-3

[0088]

[0089] It can be seen from Table 6 that the optimal doping concentration of the second p-type silicon film in the tandem solar cell structure is 1.0×10 19 cm -3 .

[0090] Example S7

[0091] like Figure 1An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0092] In the tandem solar cell S7, the thickness of the boron-doped ZnO film is 40 nm.

[0093] Comparative Examples T7-1 to T7-5

[0094] The preparation of the stacked solar cells T7-1 to T7-5 was changed to the structure described in the following Table 7. Compared with the stacked solar cell S7, only the thickness of the boron-doped ZnO film was adjusted. Other than that, the stacked solar cells T7-1 to T7-5 were prepared using the same method as the stacked solar cell S7.

[0095] Table 7 Structure and performance test results of tandem solar cells S7 and T7-1~T7-5

[0096]

[0097] It can be seen from Table 7 that in the stacked solar cell structure, the optimal thickness of the boron-doped ZnO film is 40 nm.

[0098] Example S8

[0099] like Figure 1An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0100] In the tandem solar cell S8, the doping concentration of the boron-doped ZnO film is 5.8×10 19 cm -3 .

[0101] Comparative Examples T8-1 to T8-4

[0102] The preparation of the stacked solar cells T8-1 to T8-4 ​​was changed to the structure described in the following Table 8. Compared with the stacked solar cell S8, only the doping concentration of the boron-doped ZnO film was adjusted. Other than that, the stacked solar cells T8-1 to T8-4 ​​were prepared using the same method as the stacked solar cell S8.

[0103] Table 8 Structure and performance test results of tandem solar cells S8 and T8-1~T8-4

[0104]

[0105]

[0106] Notes to Table 8: A film with a doping concentration of “0” means that the film was not doped during preparation.

[0107] It can be seen from Table 8 that the optimal doping concentration of boron-doped ZnO film in the tandem solar cell structure is 5.8×10 19 cm -3 .

[0108] Example S9

[0109] like Figure 1An amorphous silicon / microcrystalline silicon stacked solar cell is shown, which is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; wherein the flexible transparent substrate (1) is a flexible transparent polyimide film material; the front electrode (2) is an aluminum-doped ZnO film; the amorphous silicon top cell (3) is composed of a first p-type silicon film (7), a first intrinsic silicon film (8) and a first n-type silicon film (9) in order from the incident direction of light; the connecting layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; the microcrystalline silicon bottom cell (5) is composed of a third p-type silicon film (13), a second intrinsic silicon film (14) and a third n-type silicon film (15) in order from the incident direction of light; and the back electrode (6) is a metal Al film.

[0110] In the tandem solar cell S9, the thickness of the top cell is 275nm and the thickness of the bottom cell is 2680nm.

[0111] Comparative Examples T9-1 to T9-7

[0112] The preparation of the stacked solar cells T9-1 to T9-7 is changed to the structure described in the following Table 9. Compared with the stacked solar cell S9, only the thickness of the top cell and the bottom cell is adjusted. Other than this, the stacked solar cells T9-1 to T9-7 are prepared using the same method as the stacked solar cell S9.

[0113] Table 9 Structure and performance test results of tandem solar cells S9 and T9-1~T9-7

[0114]

[0115] It can be seen from Table 9 that in the stacked solar cell structure, the optimal thicknesses of the top cell and the bottom cell are 275nm and 2680nm respectively.

[0116] Comparative Example T9-8

[0117] The tandem solar cell T9-8 is an amorphous silicon / microcrystalline silicon tandem solar cell with the best performance when no connecting layer is added. The thicknesses of the top cell and the bottom cell are shown in Table 10 below.

[0118] Table 10 Structure and performance test results of tandem solar cells S9 and T9-8

[0119]

[0120] Table 11 Lighting test results of tandem solar cells S9 and T9-8

[0121]

[0122] It can be seen from Tables 10 and 11 that the new amorphous silicon / microcrystalline silicon tandem solar cell structure includes a connecting layer, the thickness of the amorphous silicon top cell is reduced, the matching degree of the top and bottom cells is improved, the conversion efficiency reaches 12.9%, and the 1000h light decay rate is within 7.5%.

[0123] The present invention is described in detail through the above specific embodiments and comparative examples, but the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, etc. made within the principle and structure of the invention should be included in the protection scope of the present invention.

Claims

1. An amorphous silicon / microcrystalline silicon tandem solar cell, characterized in that: The solar cell is composed of a flexible transparent substrate (1), a front electrode (2), an amorphous silicon top cell (3), a connecting layer (4), a microcrystalline silicon bottom cell (5) and a back electrode (6) in order from the incident direction of light; Wherein, the flexible transparent substrate (1) is a flexible transparent polyimide film material; The front electrode (2) is an aluminum-doped ZnO thin film; The amorphous silicon top cell (3) is composed of a first p-type silicon thin film (7), a first intrinsic silicon thin film (8) and a first n-type silicon thin film (9) in order from the incident direction of light; The connection layer (4) is composed of a second n-type silicon film (10), a boron-doped ZnO film (11) and a second p-type silicon film (12) in order from the incident direction of light; The microcrystalline silicon bottom cell (5) is composed of a third p-type silicon thin film (13), a second intrinsic silicon thin film (14) and a third n-type silicon thin film (15) in order from the incident direction of light; The back electrode (6) is a metal Al film; The first p-type silicon film (7) is a p-type hydrogenated amorphous silicon carbon film; The first intrinsic silicon film (8) is an intrinsic hydrogenated amorphous silicon film; The first n-type silicon film (9) is an n-type hydrogenated amorphous silicon film; The second n-type silicon film (10) is an n-type hydrogenated microcrystalline silicon film; The second p-type silicon film (12) is a p-type hydrogenated microcrystalline silicon film; The third p-type silicon film (13) is a p-type hydrogenated microcrystalline silicon film; The second intrinsic silicon film (14) is an intrinsic hydrogenated microcrystalline silicon film; The third n-type silicon film (15) is an n-type hydrogenated amorphous silicon film; The first n-type silicon film (9) and the second n-type silicon film (10) are both formed by doping phosphorus in a plasma enhanced chemical vapor deposition process, and the second n-type silicon film (10) has a higher doping concentration than the first n-type silicon film (9); the doping concentration of the second n-type silicon film (10) is 5.7×10 18 cm -3 ; The thickness of the first n-type silicon film (9) is 4 nm; the thickness of the second n-type silicon film (10) is 22 nm; The boron-doped ZnO film (11) is obtained by doping B2H6 into the reaction raw materials H2O and Zn(C2H5)2; the boron-doped ZnO film (11) has a thickness of 40 nm and a doping concentration of 5.8×10 19 cm -3 ; The second p-type silicon film (12) and the third p-type silicon film (13) are both formed by doping boron elements in a plasma enhanced chemical vapor deposition process, and the second p-type silicon film (12) has a higher doping concentration than the third p-type silicon film (13); the doping concentration of the second p-type silicon film (12) is 1.0×10 19 cm -3 ; The thickness of the second p-type silicon film (12) is 19 nm; The thickness of the third p-type silicon film (13) is 3 nm; The effective area of ​​the stacked solar cell is 2.6 cm 2 The thickness of the top cell is 275nm, the thickness of the bottom cell is 2680nm, the photoelectric conversion efficiency is 12.9%, and the light-induced degradation rate is within 7.5% after 1000h.

2. The amorphous silicon / microcrystalline silicon tandem solar cell according to claim 1, characterized in that: The preparation processes of the second n-type silicon film (10) and the first n-type silicon film (9) of the connection layer (4) are independent and are completed in different reaction chambers.

3. The amorphous silicon / microcrystalline silicon tandem solar cell according to claim 1, characterized in that: The preparation process of the second p-type silicon film (12) and the third p-type silicon film (13) is continuous, and the two films are obtained by continuously supplying reaction raw materials in a single reaction chamber and adjusting the concentration of reactants and the preparation time.

4. A method for manufacturing an amorphous silicon / microcrystalline silicon tandem solar cell according to any one of claims 1 to 3, characterized in that: The manufacturing method is implemented by using a solar cell preparation system, which includes: a cleaning system, a DC target magnetron sputtering system, a seven-chamber plasma chemical vapor deposition system, a metal organic chemical vapor deposition system, and a metal thermal evaporation system; The manufacturing method comprises the following steps: Step 1: Cut the flexible transparent polyimide film into a suitable size and tighten it on the mold. Put the mold into a cleaning container and add deionized water. Put the container into an ultrasonic cleaning machine for cleaning twice, each time for 15 minutes. After taking it out, blow dry the polyimide substrate and the mold with a nitrogen gun and put them into an oven for drying. Step 2, loading the mold into a DC target magnetron sputtering system to complete the preparation of the front electrode aluminum-doped ZnO film; Step 3: Load the mold onto the support of the loading chamber of the plasma chemical vapor deposition system, and transfer it to the p-type amorphous silicon material deposition chamber after the vacuum degree reaches the standard, to complete the preparation of the first p-type silicon film of the top cell; Step 4: Use a vacuum pump to extract the residual gas, and after the vacuum degree reaches the standard, transfer to the intrinsic amorphous silicon material deposition chamber to complete the preparation of the first intrinsic silicon film of the top cell; Step 5: Use a vacuum pump to extract the residual gas, and after the vacuum degree reaches the standard, transfer to the n-type amorphous silicon material deposition chamber to complete the preparation of the first n-type silicon film of the top cell; Step 6, using a vacuum pump to extract the residual gas, and after the vacuum degree reaches the standard, transfer to the n-type microcrystalline silicon material deposition chamber to complete the preparation of the second n-type silicon film of the connection layer; Step 7, taking the mold out of the loading chamber of the plasma chemical vapor deposition system and placing it into the metal organic chemical vapor deposition system to complete the preparation of the boron-doped ZnO film of the connecting layer; Step eight, taking the mold out of the metal organic chemical vapor deposition system, loading it into the support of the film loading chamber of the plasma chemical vapor deposition system, and transferring it into the p-type microcrystalline silicon material deposition chamber after the vacuum degree reaches the standard, to complete the preparation of the second p-type silicon film of the connecting layer; Step nine, adjusting the concentration of reactants for continuous deposition to complete the preparation of the third p-type silicon film of the bottom cell; Step 10, using a vacuum pump to extract residual gas, and after the vacuum degree reaches the standard, transfer to the intrinsic microcrystalline silicon material deposition chamber to complete the preparation of the second intrinsic silicon film of the bottom cell; Step 11, extract the residual gas with a vacuum pump, and transfer to the n-type amorphous silicon material deposition chamber after the vacuum degree reaches the standard, to complete the preparation of the third n-type silicon film of the bottom cell; Step twelve: take the mold out of the loading chamber of the plasma chemical vapor deposition system and put it into the metal thermal evaporation system to complete the preparation of the back electrode metal Al film.